2014
DOI: 10.1177/0731948714526999
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Inadequate Response to First-Grade Multi-Tier Intervention

Abstract: The purpose of this study was to use a mixed methods approach to learn about inadequate response to a year-long multi-tier RTI model that allowed first-grade students to move up and down tiers. Participants were 156 students who received supplemental intervention services during a larger multi-tier RTI study involving classrooms and 522 students across 10 schools. Findings from an all-subset regression indicate letter word reading, the fluency composite, and blending words explained the most variance (15%) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 55 publications
1
26
0
5
Order By: Relevance
“…Positive activating emotions, such as hope and enjoyment, can have a positive impact on learning, for example, through increased motivation and benefits for self-regulation and learning strategies (see also Greulich et al, 2014). Previous research has shown that increased enjoyment of learning is associated with higher achievement in math among students in seventh and eighth grades (Ahmed et al, 2013).…”
Section: Associations Between Ld Academic Emotions and Academic Achmentioning
confidence: 99%
“…Positive activating emotions, such as hope and enjoyment, can have a positive impact on learning, for example, through increased motivation and benefits for self-regulation and learning strategies (see also Greulich et al, 2014). Previous research has shown that increased enjoyment of learning is associated with higher achievement in math among students in seventh and eighth grades (Ahmed et al, 2013).…”
Section: Associations Between Ld Academic Emotions and Academic Achmentioning
confidence: 99%
“…In Al Otaiba et al (2014), Tier 3 consisted of small groups of 1–3 students. According to Greulich et al (2014), “Our interventionists expressed they wished they could have provided some one-on-one sessions to learn if…emotions could be changed through individualized attention and increased mastery” (p. 11). This primary difference between a one-on-one approach and a one-to-three approach is where we believe our study separates from previous studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is some evidence that aspects of orthographic knowledge are also predictors of reading (e.g., Georgiou, Parrila, & Papadopoulos, 2008 ;McCallum et al, 2006 ;Roberts & Mather, 1997 ). For example, in a comparison of the contribution of phonological and orthographic processing to reading ability in fi rst and second grade, Georgiou, Parrila, et al identifi ed that both processes contributed uniquely to reading ability.…”
Section: Linguistic Factorsmentioning
confidence: 99%